Isolasi Enterobacteriaceae pada Kecoa (Periplaneta americana) di Area Perumahan di Kota Cimahi - Rihibiha, Dwi; Friliansari, Lilis Puspa (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2021)
Background: Cockcroach (Periplaneta americana) is one of the common vectors found in houses, hospital, garbage dump, and other places with poor sanitation. Entrobacteriaceae, a group of Gram-negative bacteria which is mainly pathogenic, has been frequently isolated in both external and internal body of cockcroach. Thus, this study aimed to identify Enterobacteriaceae in P. americana collected from some residencies in Cimahi. Method: Isolation of bacteria on external part of P. americana, were performed according to standard procedure and isolates were further identfied with Gram staining and biochemical assay. Results: There were 19 isolates collected and result showed 13 were Enterobacteriaceae, consisted of Klebsiella sp. and Enterobacter sp. Conclusion: These findings show P. americana around some residencies in Cimahi, is a vector carrying pathogens which endanger humans.